Intracycle velocity variation of the body centre of mass in front crawl - Figueiredo, P.; Kjendlie, P.-L.; Vilas-Boas, J. P.; Fernandes, R. J. (International Journal of Sports Medicine, 2012)
Our aim was to determine the 3-dimensional intracycle velocity variation (IVV) of the body centre of mass during a 200-m front crawl event, and to analyse its relation with the segmental hand kinematics and the velocity (v) changes. 10 high-level male swimmers performed a 200-m front crawl swim at maximal intensity. 2 above- and 4 underwater cameras were used to record one complete non-breathing cycle for each 50-m lap, and APASystem was used for imaging processing. The coefficient of variation was calculated to assess the IVV in the horizontal (x), vertical (y), and lateral (z) axes; hand kinematics was also computed. IVV remained stable across the 200 m, and significant correlations were found between vx and vmaxx (r=0.55), vminx (r=0.68), IVVx (r= - 0.45), and IVVz (r= - 0.45) (all p</=.01). In addition, IVVx was correlated with the backward horizontal amplitude normalized to stroke length (r=0.54), IVVy with hand angular velocity (r= - 0.40), and IVVz with the elbow angle range in the pull phase (r= - 0.37) (all p<0.05). This study shows the stability of the IVV (x,y,z), the inverse relation of the IVV (x, z) with v, the direct relation of the vmaxx and vminx with v, and the influence of the hand kinematics in the IVV.